Prevalence and persistence of depression among undergraduate medical students: a longitudinal study at one UK medical school - Quince, Thelma A (BMJ Group, 2012)
OBJECTIVES: To determine the prevalence of depression among male and female medical students, its change over time and whether depression persists for affected students. DESIGN: Longitudinal study comprising annual questionnaire surveys which included the depression subscale of the Hospital Anxiety and Depression Scale (HADS-D). PARTICIPANTS: Between 2007 and 2010 all 1112 students entering the Core Science component (Year 1) and all 542 students entering the Clinical component (Year 4) of the Cambridge (UK) medical course were followed-up annually. METHODS: We analysed, separately for men and women, mean HADS-D scores, the proportions whose scores indicated depression at different time-points and for students maintaining participation, the number of occasions on which their HADS-D scores indicated depression. RESULTS: 725 Core Science and 364 Clinical students participated. Mean HADS-D scores ranged between 3.34 and 3.49 among all Core Science students and between 2.16 and 2.91 among all Clinical students. There was no difference between men and women in median HADS-D scores. Prevalence of depression ranged between 5.7% and 10.6% among all Core Science students and between 2.7% and 8.2% among all Clinical students. Over time Core Science students displayed no increase in mean HADS-D score. Among Clinical students only men displayed a small increase (time coefficient 0.33 (95% CI 0.11 to 0.55)). Prevalence did not increase over time. 220 Core Science and 150 Clinical students participated throughout the study. Of these, 18.2% and 10.6%, respectively, recorded HADS-D scores indicating depression on at least one occasion. Of 56 students recording depression at some point, 37 did so only once. CONCLUSIONS: Prevalence of depression among participants was similar to that reported for comparable groups. Among men approaching the end of clinical studies depression scores increased. In all years a minority of students displayed depression; for some this persisted. Mechanisms are needed to identify and support students suffering from depression, particularly when persistent.